The Advantages and Disadvantages of Phytoestrogens - Sutrisno, M.D., Ph.D, REI (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2022)
Phytoestrogens are plant-derived chemicals found in various foods, the most prominent in soy. Many health benefits are attributed to phytoestrogens, including a reduced incidence of osteoporosis, breast cancer, menopausal symptoms, and heart disease; however, many are also classified as endocrine disruptors, which can potentially create adverse health effects. As a result, whether phytoestrogens are good or hazardous to one's health has yet to be answered. The answer is likely complicated, and it could be influenced by factors, namely health, age, and the presence or absence of specific gut bacteria. Because worldwide consumption is continually expanding, clarity on this subject is required. On the other hand, phytoestrogens are frequently advertised as a natural alternative to estrogen replacement therapy and are included in various dietary supplements. Because phytoestrogens have molecular and cellular properties similar to those of artificial endocrine disruptors, such as bisphenol A (BPA), and are also weak estrogen agonists/antagonists, making them valuable models for general understanding of the biologic effects of endocrine disruptors 1–3.